Role of Financial Development in Economic Globalization: Evidence from Six Developing Countries - Amir, Farah (Journal of Accounting, Business and Finance Research, 2020)
Among different dimensions of globalization, economic globalization is one of the dimensions which involve the increased independence of different economies of the world that comes from the enhanced trade across the borders, transfer of international capital across the countries and through the increases exchange of technologies. This concept is especially important for the developing countries as they are in the process of establishment and globalization. The current study associates this concept with the financial development (FD) and the objective of the study is to investigate the impact of FD on the economic globalization (EG) in the developing countries. In this regard, the data has collected from the developing countries which include Romania, Jordan, Mauritius, Oman, Poland and Somalia. The data has been collected from the website of World Development Indicators by the World Bank for the time period of 27 years. After data collection, the researcher used different techniques and tools such as unit root test cross sectional dependence and correlation test, Granger Casualty test etc. and the desired results were obtained. The results of the current study have indicated that the both dimensions of financial development i.e. gross domestic savings and private credit has favourable impact on EG. In addition, the influence of the two control variables i.e. GDP and FDI has also been found as significant and positive. This study has the implications for the developing countries as they can get assistance in many aspects with the objective to increase globalization.